2011
DOI: 10.1002/ajmg.c.30319
|View full text |Cite
|
Sign up to set email alerts
|

Amelia: A multi‐center descriptive epidemiologic study in a large dataset from the International Clearinghouse for Birth Defects Surveillance and Research, and overview of the literature

Abstract: This study describes the epidemiology of congenital amelia (absence of limb/s), using the largest series of cases known to date. Data were gathered by 20 surveillance programs on congenital anomalies, all International Clearinghouse for Birth Defects Surveillance and Research members, from all continents but Africa, from 1968 to 2006, depending on the program. Reported clinical information on cases was thoroughly reviewed to identify those strictly meeting the definition of amelia. Those with amniotic bands or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 57 publications
2
54
0
9
Order By: Relevance
“…These changes in trends are well documented in these countries where birth defect registries exist (Bermejo-Sánchez et al ., 2011). In most developing countries especially in Africa, the proportions of birth defects are unknown and contribution to mortality rates are yet to be established.…”
mentioning
confidence: 64%
“…These changes in trends are well documented in these countries where birth defect registries exist (Bermejo-Sánchez et al ., 2011). In most developing countries especially in Africa, the proportions of birth defects are unknown and contribution to mortality rates are yet to be established.…”
mentioning
confidence: 64%
“…Absence of limb(s) or congenital amelia is a rare birth defect. A multi-center descriptive epidemiologic international study by Bermejo-Sanchez et al 27 found a total prevalence of Amelia (either one or more limbs) to be 1.41 per 100,000 births. In the Bermejo-Sanchez study absence of both lower extremities accounted for approximately 10% of all amelia cases.…”
Section: Resultsmentioning
confidence: 99%
“…In another article of this issue devoted to the study of amelia in the International Clearinghouse for Birth Defects Surveillance and Research (ICBDSR) [Bermejo‐Sánchez et al, 2011], the processes of human limb development are described in detail. Briefly, the human limb development initiates in the 26th day after fertilization for the upper limb, and day 28 for the lower limb, and extends until day 56 both for the upper and the lower limbs.…”
Section: Embryology Of the Limbsmentioning
confidence: 99%
“…This subject is also detailed in the article on amelia in this issue [Bermejo‐Sánchez et al, 2011]. The genetic processes that control limb development are complicated and still not fully understood, but several gene families are known to be involved in the spatially and temporally coordinated growth and differentiation of the developing limb.…”
Section: Molecular Embryologymentioning
confidence: 99%